Logitech’s Mouse / Nadiatul Wahidah Khalid - Khalid, Nadiatul Wahidah (2022)
The company is based in Switzerland. Since 1981, the technology is focused on quality and innovation. In this company analysis, Logitech focused more on computer peripherals including mice and keyboard with attractive and modern design. Other than that, they also prepared presentation and video conferencing device with variety of design that will suit any user will’s. Plus, for better quality of video, they also have both Bluetooth head seat and speakers. But, sure in order to develop their technological advances, some of things definitely miss out. The first thing Logitech miss out is their products come with wire. Wire will burden the user as the user need extra space for do their work. User also having trouble to setup their work table due to the length of wire. User also having trouble to plug in another device such as keyboard or mouse because some PC or laptop do not come with extra USB cable port. In addition, the products have disturbing sound. When the user use the product, the sound of the product will irritate them or others. There a few alternative to the problems. First, the product use detachable and adjustable wire. User can detach the wire and adjust the length of the wire. Also, the product use USB unifying receiver which is only use one unifying receiver to connect the laptop with mouse or keyboard. It will save the space and only use o USB cable port. Second, product use high performance material and rubber wheel .The high performance material will absorb sound and make the product less noisy. Also, the rubber wheel will make the movement of the product smooth and easy. All of these alternative will help Logitech in producing quality product to customers.